The Effect of Board of Directors and Independent Board of Commissioners on Financial Performance of Banking Company - Selvi Wahyuni; Riri Mayliza (Lembaga Riset dan Inovasi Al-Matani, 2023)
The company's financial performance is a financial report that shows the condition of a company, which is used as a consideration for taking further action. as well as for the community to assess the smooth running of a company before taking action. As the manager of the company, the manager knows more about the company's prospects and internal information in the future than the owner or (shareholder). Managers have an obligation to give a signal about the condition of the company to the owner of the company. The purpose of this study was to determine the effect of independent boards of directors and commissioners on the financial performance of banking companies. The variables in this study are the Independent Board of Directors and Board of Commissioners. Sampling using purposive sampling technique with certain criteria. Which resulted in a sample of 28 banking companies listed on the Indonesia Stock Exchange in 2017-2021. The method used in this research is panel data regression analysis using Eviews version 8. The results show that the Board of Directors has no effect on the company's financial performance, while the Board of Independent Commissioners has an influence on the company's financial performance.